2003
DOI: 10.2172/811962
|View full text |Cite
|
Sign up to set email alerts
|

Unified Ideal Stability Limits for Advanced Tokamak and Spherical Torus Plasmas

Abstract: Ideal magnetohydrodynamic stability limits of shaped tokamak plasmas with high bootstrap fraction are systematically determined as a function of plasma aspect ratio. For plasmas with and without wall stabilization of external kink modes, the computed limits are well described by distinct and nearly invariant values of a normalized beta parameter utilizing the total magnetic field energy density inside the plasma. Stability limit data from the low aspect ratio National Spherical Torus Experiment is compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…q min is well above unity) and that the rotation shear is below the threshold for destabilizing a KH mode, as discussed in section 4. To use equation (1) for extrapolation to future devices, an expression for β static N can be taken from scalings with aspect ratio, I p /aB, shaping, pressure peaking, internal inductance and so on, as given in references [19] or [20] for instance. …”
Section: The Effect Of Rotation On the Pressure Limitmentioning
confidence: 99%
See 1 more Smart Citation
“…q min is well above unity) and that the rotation shear is below the threshold for destabilizing a KH mode, as discussed in section 4. To use equation (1) for extrapolation to future devices, an expression for β static N can be taken from scalings with aspect ratio, I p /aB, shaping, pressure peaking, internal inductance and so on, as given in references [19] or [20] for instance. …”
Section: The Effect Of Rotation On the Pressure Limitmentioning
confidence: 99%
“…At such large sheared rotation velocities, magnetic Kelvin-Helmholtz (KH) instabilities [17] become a concern, as recently observed in a magnetized plasma in the solar corona [18]. In the same way that previous studies have investigated shaping or aspect ratio effects to optimize fusion power plant design [19,20], here we assess the effects of strong rotation on stability limits in tokamak plasmas. In section 2 we provide details of the numerical tools used and the plasma equilibria studied, before describing the effects of rotation on the pressure limit in section 3.…”
Section: Introductionmentioning
confidence: 98%
“…One of the key results of Reference [22] is the finding that the no-wall stability limit set by ballooning and low-n kink modes is β N ≈ 3.1 ± 0.3 for cylindrical kink safety factor q * ≥ 1.7. The computed limit was found to hold for shaped tokamak plasmas over a wide range of aspect ratios.…”
Section: Ideal Kink Stability Limits At High β Pmentioning
confidence: 99%
“…Recent theoretical work has shown that β N ∼ 3 describes the no-wall ideal MHD external kink limit for a large range of q * ≡ (1 + κ 2 )πaB t0 /µ 0 I p and aspect ratio, as shown in recent theoretical work [15].…”
Section: High β Plasmas -Effect Of Shapingmentioning
confidence: 59%